1998
DOI: 10.1525/maq.1998.12.4.490
|View full text |Cite
|
Sign up to set email alerts
|

Willing the Spirits to Reveal Themselves: Rural Kenyan Mothers' Responsibility to Restore Their Children's Health

Abstract: Women's contributions to the improvement and maintenance of health are being acknowledged the world over. Recent studies show that most health care is domestic and that women provide nearly 95 percent of this care. Their role as healers, nurses, doctors, folk practitioners, and lay therapists has also been recognized. This research report analyses exorcism as a special function performed by Duruma mothers on behalf of their ailing children. The women represent their children and identify the spirit(s) responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…The importance of costs of accessing care at health units noted in this study has also been documented elsewhere as a significant factor determining treatment-seeking practices (Beckerleg, 1994;Amuyunzu, 1998;Nyamongo, 2001). These studies have shown that pregnant women make an assessment of several factors including costs before a treatment choice is made.…”
Section: Discussionsupporting
confidence: 73%
“…The importance of costs of accessing care at health units noted in this study has also been documented elsewhere as a significant factor determining treatment-seeking practices (Beckerleg, 1994;Amuyunzu, 1998;Nyamongo, 2001). These studies have shown that pregnant women make an assessment of several factors including costs before a treatment choice is made.…”
Section: Discussionsupporting
confidence: 73%
“…The pattern of seeking care at health units and laboratory investigations is similar to previous findings on treatment seeking for malaria (6,10,27). It is not known whether self-treatment with inappropriate drugs and dosages leads to complete recovery or leads to reoccurrence of malaria and hence described as persistent.…”
Section: Discussionsupporting
confidence: 76%
“…In many rural African settings, gender - its intersectionality with other social axes - and family relations; strongly influence treatment decision-making processes for child illness [ 17 19 , 27 , 28 , 33 ]. Women are often held responsible for the health of their children, but many household members and other social network members can be involved in treatment seeking actions [ 17 , 18 , 23 , 26 , 33 35 ]. Whether or not mothers make independent decisions in relation to child illnesses is determined by a range of inter-related factors including: the nature and perceived severity of illness; who is perceived to own the child; what is perceived to have caused the illness; and intra-household roles and relations [ 27 , 28 , 33 ].…”
Section: Introductionmentioning
confidence: 99%